"Assessment of the competence formation in the security and protection of intellectual property rights field among employees of general secondary education institutions by means of qualimetry. - Lunіachek V.; Ruban, N.; Kravchuk, N. (Problems of Engineer-Pedagogical Education, 2021)
The paper presents materials that highlight the process of assessing the employees competence of general secondary education institutions in the field of intellectual property by means of qualimetry, which is an important component of the positive dynamics of their integral competence in the context of innovative development of education. The works of domestic and foreign scientists on pedagogical qualimetry, who are actively involved in the development of factor-criterion models for assessing individual competencies of pedagogical and scientific-pedagogical workers are considered in detail. The urgency of the creation of procedures for measuring the formation of individual competencies of teachers in the framework of the formation and improvement of their integral professional competence in the course of life has been proved. The work created a procedure for measuring the level of employees competence formation of general secondary education institutions (UESO) in a specific area - the sphere of security and protection of intellectual property rights. The authors have developed a factor-criterion model "Assessment of the teacher competence formation level of educational institutions in the intellectual property field ". The model shows the competencied factors that were previously declared by the authors in the competence model of the teacher of the USE in the intellectual property field, and the criteria are formulated based on the structure of each competence, that is, the corresponding knowledge, skills, abilities and other personal and professional qualities. The use of tools for determining criteria is described. Assessment experts in the process of constructing and using the developed factor-criterion model were the leading specialists in the field of intellectual property, who are also the leading specialists in the field of education. To understand the measurement procedure, according to individual criteria, several examples of the instruments are given. It is noted that an important aspect of a comprehensive solution to the issue of introducing a qualimetric approach in the education system is the introduction of relevant academic disciplines into the curricula for training specialists in higher education institutions of a pedagogical direction is advisable to conduct special training seminars for heads of educational institutions on the introduction of a qualimetric approach into their practice.